Lithium compounds as single site catalysts for hydroboration of alkenes and alkynes - Bisai, Milan Kumar; Yadav, Sandeep; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2019)
The hydroboration of alkenes and alkynes using easily accessible lithium compounds [2,6-di-tert-butyl phenolatelithium (1a) and 1,1 ` dilithioferrocene (1b)] has been achieved with good yields, high functional group tolerance and excellent chemoselectivity. Deuterium-labeling experiments confirm the cis-addition of pinacolborane. The methodology has been further extended to myrcene, which undergoes selective 4,3-hydroboration. DFT calculations provide insights into the mechanism.

Lithium compound catalyzed deoxygenative hydroboration of primary, secondary and tertiary amides - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2021)
A selective and efficient route for the deoxygenative reduction of primary to tertiary amides to corresponding amines has been achieved with pinacolborane (HBpin) using simple and readily accessible 2,6-di-tert-butyl phenolate lithium center dot THF (1a) as a catalyst. Both experimental and DFT studies provide mechanistic insight.